Examining the Practice of Voluntary Disclosure Programs for Individual Taxpayers - Wiranata, Ni Made Peramini Sagita; Musmini, Lucy Sri; Atmadja, Anantawikrama Tungga (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to explain taxpayers’ perceptions of the Voluntary Disclosure Program (VDP) and its implementation practices. A qualitative approach with a critical paradigm was employed to explore the VDP phenomenon, which continues to generate debate, particularly from the taxpayers’ perspective. Data were collected through observation, interviews, and documentation involving 12 informants, consisting of eight taxpayers, two tax consultants, and two tax officers. Data analysis followed an interactive model comprising data collection, data reduction, data display, and conclusion drawing. The findings indicate several factors that discourage taxpayers from participating in the VDP, including a lack of trust in the tax system, concerns about tax rates, the perception that there are no undisclosed tax obligations, as well as psychological factors and fear. Insufficient information regarding the benefits and procedures of the VDP also contributes to non-participation. Interestingly, taxpayers who participated in the VDP did not fully support the program; many joined merely to demonstrate formal compliance with regulations, despite having no genuine intention or moral willingness to participate. These findings highlight the importance of strengthening trust, enhancing understanding, and improving the socialization of the VDP to encourage conscious and genuinely voluntary taxpayer participation.